Practice of integrated treatment process for acute ischaemic stroke in hospital coordinated by emergency stroke nurses - Dongmei Li; Hongjian Zhang; Xiaoying Lu; Lingjuan Zhang; Jianmin Liu (Wiley, 2022)
Abstract Aims To explore the practice effect of establishing an integrated treatment process by stroke emergency nurses in general hospitals for acute ischaemic stroke (AIS). Design Compared the time spent in each link before and after the establishment of AIS integrated treatment. Methods Since March 2016, we set up a team of emergency stroke nurses (ESN), trained and assessed the knowledge of emergency stroke, and set up a post of ESN. Results The median time of admission‐judgement, admission‐establishment of venous access, admission‐cranial CT examination and admission‐intravenous thrombolytic therapy was statistically significantly shortened after the implementation of the integrated treatment process of AIS coordinated by stroke emergency nurses (p < .01). The new treatment process of AIS further shortens the time of each treatment link and promotes the timeliness.